2011
DOI: 10.1021/cg201067q
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Octamer Water Cluster and 1D T5(2) Water Tape Trapped in Two Luminescent Zn(II)/1,2-Bis(imidazol-1′-yl)ethane/Dicarboxylate Hosts: From 2D (4,4) Net to 3D 5-Fold Interpenetrated Diamond Network

Abstract: Two new mixed-ligand Zn(II) coordination polymers, namely, [Zn(bime)(glu)·4H2O] n (1) and [Zn(bime)(sub)·3H2O] n (2) (bime = 1,2-bis(imidazol-1′-yl)ethane, H2glu = glutaric acid, H2sub = suberic acid), have been synthesized and structurally characterized. Complex 1 exhibits a wavy two-dimensional (2D) sheet with (4,4) topology. Complex 2 is a three-dimensional (3D) framework with 5-fold interpenetrated diamond topology. Of particular interest, a discrete octamer water cluster comprised of a chairlike hexamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 124 publications
3
18
0
Order By: Relevance
“…Bond lengths and angles of Zn center are given in Table . The Zn‐O distances are 1.9528(14) and 1.9780(15) Å, and Zn‐N distances are 2.0346(17) and 2.0378(17) Å, which are in agreement with those observed in other structures . The maximum and minimum bond angles for Zn are 133.84(5) and 99.75(6)°, with an average of 109.02(8)°, which slightly deviates from the angle of 109.47° in a perfect tetrahedron.…”
Section: Resultssupporting
confidence: 83%
“…Bond lengths and angles of Zn center are given in Table . The Zn‐O distances are 1.9528(14) and 1.9780(15) Å, and Zn‐N distances are 2.0346(17) and 2.0378(17) Å, which are in agreement with those observed in other structures . The maximum and minimum bond angles for Zn are 133.84(5) and 99.75(6)°, with an average of 109.02(8)°, which slightly deviates from the angle of 109.47° in a perfect tetrahedron.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, it is observed that the octameric chain of water is encapsulated between the hydrogen-bonded 2D sheets of the dimeric units of 1 through strong hydrogen bonding (as shown in Figure 6). In 1 , the O···O distance varies from 2.6620 to 2.7492 Å; these parameters are comparable to those for ice, where the O···O distance is 2.783 Å 25,48,49 and the O···O···O angles vary from 96.64 to 152.09°. This arrangement enhances the stability of the water chain as evident from the thermal behavior of 1 (vide infra).…”
Section: Resultssupporting
confidence: 53%
“…The solid‐state photoluminescence spectra of CPs 1 and 2 and ligand L are shown in Figure . It is known that the π*→n electron transition in carboxylate acid is far weaker than the π*→π electron transition in the L ligand . Therefore, the photoluminescence phenomena of CPs 1 and 2 are mainly related to metal ions and the N‐donor ligand.…”
Section: Resultsmentioning
confidence: 99%